Antibacterial and anticancer properties of Solanum mauritianum fruit components analyzed using LC-QTOF-MS/MS - Abraham Goodness Ogofure; Tendani Sebola; Ezekiel Green (Scientific Reports)
Abstract This study evaluated the antibacterial and anticancer properties of S. mauritianum fruit components through LC-QTOF-MS/MS metabolomic profiling. The samples were extracted, and the antibacterial activity was conducted using a standard Resazurin microtiter assay. The minimum inhibitory concentrations (MICs) of the crude extracts were evaluated against reference pathogenic bacterial isolates. The anticancer activity of the extracts was tested against U-87 MG glioblastoma and A549 lung carcinoma cells (ATCC cancer cell lines). The real-time toxicity assay and comprehensive metabolomic profiling were evaluated for the crude extracts. Results revealed that the ripe fruit coat exhibited the richest chemical diversity, with 15 unique metabolites, while the unripe fruit had 5. Detailed classification of the identified metabolites showed that alkaloids accounted for 33.3%, followed by terpenoids (21.2%). The extracts of the fruit components had significant antibacterial activity against the referenced pathogens of public health importance. Extracts from the ripe fruit coat demonstrated significant cytotoxicity on U-87 MG glioblastoma cell viability, suggesting potential anticancer activity, while the effect on A549 lung carcinoma cells showed high viability across all treatments. The real-time cytotoxicity assays further highlighted the dose-dependent inhibition of glioblastoma cells by crude extracts from the ripe fruit coat, emphasizing its therapeutic potential.